2013
DOI: 10.13037/gr.vol28n84.1280
|View full text |Cite
|
Sign up to set email alerts
|

Análise do Comprometimento Organizacional e sua Natureza em Relação aos Funcionários Públicos Municipais

Abstract: The aim of this article is to identify the type of organizational commitment of the employees of the municipal government of the city of Pitanga in Parana state, focusing the multidimensional model of commitment described by Meyer and Allen (1990, 1991and 1993 which analyses three factors of organizational commitment: affective, normative and instrumental. We performed an exploratory research, being presented a compared diagnostic between factors of commitment. The universe consisted of 50 effective employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 1 publication
(1 reference statement)
1
5
0
10
Order By: Relevance
“…In the studies found, most of the diagnoses of organizational impairment were carried out in several organizations (Schmidt & Pinheiro, 2003;Moraes & Costa, 2007;Yoshitake, Fraga, Torres, & Passos, 2009;Botelho & Paiva, 2010;Roman, Stefano, Andrade, & Zampier, 2012;Paiva, La Falce, &De Muylder, 2013 andSoares &Fleck, 2014). It is interesting to note that such diagnostic studies were carried out in both public and private organizations, with the Meyer, Allen, and Smith (1993) model prevailing, attesting its applicability in national studies.…”
Section: Theoretical Referencementioning
confidence: 91%
See 2 more Smart Citations
“…In the studies found, most of the diagnoses of organizational impairment were carried out in several organizations (Schmidt & Pinheiro, 2003;Moraes & Costa, 2007;Yoshitake, Fraga, Torres, & Passos, 2009;Botelho & Paiva, 2010;Roman, Stefano, Andrade, & Zampier, 2012;Paiva, La Falce, &De Muylder, 2013 andSoares &Fleck, 2014). It is interesting to note that such diagnostic studies were carried out in both public and private organizations, with the Meyer, Allen, and Smith (1993) model prevailing, attesting its applicability in national studies.…”
Section: Theoretical Referencementioning
confidence: 91%
“…It is interesting to note that such diagnostic studies were carried out in both public and private organizations, with the Meyer, Allen, and Smith (1993) model prevailing, attesting its applicability in national studies. In addition, the studies of Botelho and Paiva (2010) and Paiva, La Falce, and De Muylder (2013), who applied the model in public organizations, obtained results that were antagonistic to those of Roman, Stefano, Andrade, and Zampier (2012): in the first studies, calculative impairment was evidenced in public organizations, and in the latter, effective commitment was more evident. In addition, the need for other investigations on commitment in public organizations was indicated to understand the peculiarities of the phenomenon in such context better.…”
Section: Theoretical Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the work by Spector (2006), Roman et al (2012) divided the nine dimensions of satisfaction into three groups: a) Rewards: salary, promotion opportunities, and benefits; b) Relationship: supervision, co-workers, and working conditions; c) Nature of work: nature of work, communication, and safety. From this classification by Roman et al (2012), one dimension of each group was chosen for this research.…”
Section: Satisfaction With Workmentioning
confidence: 99%
“…From this classification by Roman et al (2012), one dimension of each group was chosen for this research. From the Rewards group, promotion Commitment to Work and its Relationship with Organizational Culture Mediated by Satisfaction opportunities was chosen, which means the individual's level of contentment with the possibilities offered by the company to progress in their career, involving both the position and the time that elapses between promotions and their criteria.…”
Section: Satisfaction With Workmentioning
confidence: 99%